The Principles of Legal Certainty for Land Rights After Natural Disaster in Indonesia - Rachmah, Andriana; Sudiro, Amad (Journal of Law, Politic and Humanities, 2024)
This paper explores the principles of legal certainty for community land rights in the subsequent to the occurrence of catastrophic natural events in Indonesia, it probes into the intricacies of land ownership and the challenges faced by communities when their lands are devastated by natural calamities. The research scrutinizes the jurisprudential structure of Indonesia, its efficacy, and the lacunae present in the protection of property rights amidst such calamities. It additionally deliberates on the functions of governmental and non-governmental entities, and international bodies in ensuring legal certainty for affected communities. The paper concludes with recommendations for policy changes and legal reforms to augment the safeguarding of communal property rights in the advent of catastrophic natural events. This research contributes to the discourse on land rights and legal certainty, providing valuable insights for policymakers, legal practitioners, and disaster management agencies.